Neem: A Tree for Solving Global Problems - National Research Council (The National Academies Press, 1992)
The neem tree, one of the most promising of all plants, may eventually benefit every person on the planet. Probably no other plant yields as many varied products or has as many exploitable by-products. Indeed, as foreseen by some scientists, this tree may usher in a new era in pest control; provide millions with inexpensive medicines; cut the rate of population growth; and perhaps even reduce erosion, deforestation, and the excessive temperature of an overheated globe. On the other hand, although the enthusiasm may be justified, it is largely founded on exploratory investigations and empirical and anecdotal evidence. The purpose of this book is to marshal the various facts about this little-known species, to help illuminate its future promise, and to speed realization of its potential.
Keywords: Biology and Life Sciences

Lost Crops of the Incas: Little-Known Plants of the Andes with Promise for Worldwide Cultivation - National Research Council (The National Academies Press, 1989)
This fascinating, readable volume is filled with enticing, detailed information about more than 30 different Incan crops that promise to follow the potato's lead and become important contributors to the world's food supply. Some of these overlooked foods offer special advantages for developing nations, such as high nutritional quality and excellent yields. Many are adaptable to areas of the United States. Lost Crops of the Incas includes vivid color photographs of many of the crops and describes the authors' experiences in growing, tasting, and preparing them in different ways. This book is for the gourmet and gourmand alike, as well as gardeners, botanists, farmers, and agricultural specialists in developing countries.
Keywords: Agriculture; Biology and Life Sciences

Vetiver Grass: A Thin Green Line Against Erosion - National Research Council (The National Academies Press, 1993)
For developing nations, soil erosion is among the most chronic environmental and economic burdens. Vast amounts of topsoil are washed or blown away from arable land only to accumulate in rivers, reservoirs, harbors, and estuaries, thereby creating a double disaster: a vital resource disappears from where it is desperately needed and is deposited where it is equally unwanted. Despite much rhetoric and effort, little has been done to overcome this problem. Vetiver, a little-known tropical grass, offers one practical and inexpensive way to control erosion on a huge scale in both humid and semi-arid regions. Hedges of this deeply rooted species catch and hold back sediments while the stiff foliage acts as a filter that also slows runoff and keeps moisture on site. This book assesses vetiver's promise and limitations and identifies places where this grass can be deployed without undue environmental risk.
Keywords: Agriculture

Food Aid Projections for the Decade of the 1990s - National Research Council (The National Academies Press, 1988)
This book presents the results of a meeting held by the Board on Science and Technology for International Development. At this meeting, six groups of modelers presented their best estimates of the food aid/food commodity trade picture during the period 1991-2000. These estimates are based on each modeler's own database and own assumptions about trends in global policy, climate, population, and economics.
Keywords: Food and Nutrition

Sustainable Agriculture and the Environment in the Humid Tropics - National Research Council (The National Academies Press, 1993)
Rainforests are rapidly being cleared in the humid tropics to keep pace with food demands, economic needs, and population growth. Without proper management, these forests and other natural resources will be seriously depleted within the next 50 years. Sustainable Agriculture and the Environment in the Humid Tropics provides critically needed direction for developing strategies that both mitigate land degradation, deforestation, and biological resource losses and help the economic status of tropical countries through promotion of sustainable agricultural practices. The book includes:
Keywords: Environment and Environmental Studies